Physcion 8-O-β-glucopyranoside induces mitochondria-dependent apoptosis of human oral squamous cell carcinoma cells via suppressing survivin expression - Liu Meng-dong; Xiong Shi-jiang; Tan Fei; Liu Yi (Acta Pharmacologica Sinica; Vol 37, No 5 (May 2016): Acta Pharmacologica Sinica, 2017)
Aim: A previous study has shown that physcion 8-O-β-glucopyranoside (PG) derived from Rumex japonicas Houtt causes apoptosis and blocks cell cycle progression in human lung cancer cells. In the present study we investigated the molecular mechanisms underlying PG-induced cancer cell apoptosis. Methods: Human OSCC-derived cell line KB was treated PG (10, 20, 50 μg/mL). Cell apoptosis was detected with flow cytometry. Mitochondrial membrane potential (MMP) and release of cytochome C from mitochondria were measured; the expression of relevant signaling proteins was analyzed using Western blotting or qRT-PCR. For evaluation of in vivo anticancer action, nude mice grafted with KB cells were treated with PG (10, 20, 40 mg·kg−1·d−1, ip) for 24 days. Results: PG dose-dependently suppressed cell proliferation and induced apoptosis in KB cells. PG-induced apoptosis was mediated via the intrinsic mitochondrial pathway, as evidenced by the decreased Bcl-2, increased Bax and Bax/Bcl-2 ratio, as well as the loss of MMP, caspase-9 activation, and increased cytosolic cytochrome c. Furthermore, PG suppressed the expression of survivin, whereas overexpression of survivin markedly attenuated PG-induced apoptosis. Meanwhile PG increased the expression of tumor suppressor PTEN, and decreased p-Akt, p-GSK3β and miR-21 levels. Pharmacological activation of Akt/GSK3β signaling or transfection with miR-21 mimic abolished PG-induced survivin reduction and cell apoptosis. Similar results were observed in PG-treated nude mice grafted with KB cells. Conclusion: Physcion 8-O-β-glucopyranoside induces mitochondria-dependent apoptosis of human OSCC cells by suppressing survivin expression via miR-21/PTEN/Akt/GSK3β signaling pathway.